2011
DOI: 10.1186/1471-2482-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Malignant PEComa: a case report with emphasis on clinical and morphological criteria

Abstract: BackgroundMalignant perivascular epitheliod cell tumor (PEComa) is a very rare entity composed of distinctive perivascular epitheliod cells with variable immunoreactivity for melanocytic and muscle markers. At present this neoplasm does not have a known normal cellular counterpart and the natural history is often unpredictable. Up to now, few cases of PEComa have been described and treatment modalities are still controversial, particularly in advanced conditions.Case presentationWe handled the case of a 42-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 11 publications
(20 reference statements)
2
34
0
1
Order By: Relevance
“…A recent case by Slevaggi et al reported 25 day mortality in a 42 year old male with a malignant PEComa which was hepatic in origin. 7 This has reflected our own experience in the case outlined here with our patient not surviving greater than 3 months since diagnosis.…”
Section: Discussionsupporting
confidence: 54%
“…A recent case by Slevaggi et al reported 25 day mortality in a 42 year old male with a malignant PEComa which was hepatic in origin. 7 This has reflected our own experience in the case outlined here with our patient not surviving greater than 3 months since diagnosis.…”
Section: Discussionsupporting
confidence: 54%
“…They are primarily benign tumours, but they may rarely behave malignantly 12. Clinical manifestations of PEComa in general, including hepatic PEComa, are uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…A second hypothesis is that PEC has a myoblastic, smooth muscle origin with a molecular alteration that leads to the expression of melanogenesis and melanocytic markers; a third hypothesis is that PEC has a pericytic origin [7,30].…”
Section: Introductionmentioning
confidence: 99%